TVET Trainers Understanding of Engaging Instruction: Supportive Learning Environment for Work Integrated Learning - Gouhar Pirzada (UMT Education Review, 2022)
The purpose of this study is to explore TVET trainers’ understanding of engaging instruction with relevance to ensuring a supportive learning environment that could lead to effective work-integrated learning. Participants’ engagement in the training process that wholly prepares them for real-life work scenarios is always a challenging task for trainers. The existing gaps in theory and practice highlight the significance of the research study. Both the trainees and the trainers are usually not content with the learning environment and the final training outcomes to match their work requirements. This research identifies the trainer’s understanding of engaging instruction under three main themes: supportive learning environment, work-integrated learning, and expected competencies of trainers. Purposive sampling was used to collect data from 21 TVET trainers. All participants are actively working in TVET institutes. The qualitative data analysis technique is applied as a data collection strategy to explore participants' views, opinions, practices, challenges, preferences, and lived experiences. The data analysis revealed that most trainers believe training participants require a conducive environment to enrich their learning experiences. Most participants have also emphasised achieving the work-integrated learning outcomes by applying the KSA (Knowledge, Skills and Attitude) approach. The findings have been discussed from various perspectives, and some suggestions based on results have been put forward, including a further focus on appropriate training strategies.  Keywords: Supportive learning environment, work-integrated learning, engaging instructions; trainers’ competencies, TVET